2018
DOI: 10.1002/fsn3.803
|View full text |Cite
|
Sign up to set email alerts
|

Composition and biochemical properties of l‐carnitine fortified Makgeolli brewed by using fermented buckwheat

Abstract: Makgeolli is a traditional Korean alcoholic rice beverage. It is brewed of ingredients containing starch, Nuruk, and water. In order to improve the quality and functionality of Makgeolli, the Rhizopus oligosporus fermented buckwheat containing 18.7 mg/kg of l‐carnitine were utilized to brew l‐carnitine fortified Makgeolli with rice. Makgeolli was prepared in two‐stage fermentation method and total rutin and quercetin in each fermented buckwheat Makgeolli were increased 1.8‐fold greater than buckwheat Makgeolli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…R. oligosporus was isolated from our previous study [26,27,37] and cultured on potato dextrose agar (PDA, Difco, Detroit, MI, USA) medium at 30 • C for 3 days to obtain spores. Wild ginseng powder was sterilized at 121 • C for 15 min.…”
Section: Fermentation Of Wild Ginseng By R Oligosporusmentioning
confidence: 99%
See 1 more Smart Citation
“…R. oligosporus was isolated from our previous study [26,27,37] and cultured on potato dextrose agar (PDA, Difco, Detroit, MI, USA) medium at 30 • C for 3 days to obtain spores. Wild ginseng powder was sterilized at 121 • C for 15 min.…”
Section: Fermentation Of Wild Ginseng By R Oligosporusmentioning
confidence: 99%
“…Rhizopus oligosporus (R. oligosporus), a fungus found predominantly in fermented soybean products such as Indonesian tempeh, hydrolyzes protein into amino acids and small peptides by various enzymes such as lipase, amylase, protease and glucoamylase, and synthesizes l-carnitine and γ-aminobutyric acid (GABA) in soybean, buckwheat and quinoa [25][26][27]. l-carnitine plays an important role in the transportation of fatty acids into the mitochondrial compartment for β-oxidation and subsequent energy production and antioxidant activity to prevent peroxidative damage [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…It produces various enzymes including amylase, protease, glucoamylase, and lipase, as well as carbohydrate-cleaving enzymes including xylanase, β-glucuronidase, and β-glucosidase to synthesize l -carnitine, γ-aminobutyric acid (GABA), and polyphenols during fermentation ( Huynh et al, 2014 , McCue and Shetty, 2003 ). Recently, we reported improvement of l -carnitine, GABA, and bioactive phenolic compound contents, as well as the biological properties of quinoa, ginseng, and buckwheat through SSF using R. oligosporus ( Hur et al, 2018 , Lee et al, 2020 , Park et al, 2018 ). Moreover, coffee fermented via SSF using R. oligosporus had improved aroma and sweetness ( Lee, Cheong, Curran, Yu, & Liu, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to glucose and fructose, maltose were also utilized by yeast to generate alcohols, and the reduction of these sugars impart a specific taste to Makgeolli with mineral and vitamin nutrients (Kim et al, 2013). Park et al (2018) reported L-carnitine fortified Makgeolli using fermented buckwheat. During Makgeolli brewing, increasing contents of L-carnitine and biogenic flavonoids in buckwheat promote the health benefits and effectively increase the alcohol production.…”
Section: Flavor Varieties In Makgeolli and Health Benefitsmentioning
confidence: 99%